ChemInform Abstract: A Study of the Al—Pt—Ir Phase Diagram. Issue 44 (15th October 2015) - Grushko, B.; Samuha, S.; Meshi, L.
Abstract Phase equilibria in the Al—Pt—Ir ternary system are studied for ≤50 at.% Al at 1100 °C, ≤70 at.% Al at 900 C, and ≤75 at.% Al at 810 °C through levitation induction melting of the elements followed by annealing at the mentioned temperature for 146‐306 h.